Dually functional polyethylenimine-coated gold nanoparticles: a versatile material for electrode modification and highly sensitive simultaneous determination of four tumor markers - Thitirat Putnin (2019)
© 2019, Springer-Verlag GmbH Austria, part of Springer Nature. A novel sandwich-type electrochemical multiplex immunoassay is described for simultaneous detection of the tumor biomarkers alpha fetoprotein (AFP), carcinoembryonic antigen (CEA), prostate-specific antigen (PSA) and interleukin-8 (IL-8). Polyethylenimine-coated gold nanoparticles (PEI-AuNPs) were used for both modification of a screen-printed carbon electrode (SPCE) and as labeling tags. The coated AuNPs can be easily adsorbed on the electrodes which also are loaded with the electroactive metal ions cadmium(II), lead(II) copper(II) and silver(I) and related secondary antibodies (Ab 2 ). These give distinct voltammetric signals at −0.80, −0.55, −0.20 and + 0.05 V, respectively (vs Ag/AgCl). Four corresponding capture antibodies (Ab 1 ) were then conjugated to one of the electrodes. After a sandwich-type structure was formed by binding of the analytes and the labeling AuNPs, the electrochemical signal responses were recorded. Under the optimized testing conditions, there is a linear relationship in range from 0.25–10 ng mL −1 for AFP, CEA and PSA, and from 0.50–100 pg mL −1 for IL-8. The corresponding detection limits are 1.7, 1.6, 0.9 and 1.0 fg mL −1 , respectively. Cross reactivity, interferences and stability of the modified electrodes and of the signal nanotags are satisfying in that they can be stored for >4 weeks without significant signal reduction. The method was successfully applied to the determination of the biomarkers in spiked human serum. [Figure not available: see fulltext.].